PERBAIKAN KUALITAS MORFOLOGI SPERMATOZOA TIKUS WISTAR (Rattus norvegicus) JANTAN DIABETIK DENGAN PEMBERIAN EKSTRAK DAUN ASAM JAWA (Tamarindus indica L.) - Afifah, Delta Aulia; Fauziah, Cut; Simanjuntak, Kristina; Amalia, Muttia (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Diabetes mellitus (DM) increases free radicals that can cause complications of several organs, including reproductive organ that cause abnormalities in sperm morphology. Damage caused by ROS can be treated with antioxidant compounds that are widely found in plants, including tamarind leaves. This study was aimed to see the improvement in sperm morphology of diabetic rats given tamarind leaf extract. This experimental study used a true experimental method with post-test only control group design. The samples were 30 male Wistar strain white rats aged 10-12 weeks, weighing 150-200 grams. Rats were selected through simple randomization method and divided into 5 groups. K1 was given standard drinking food, K2 was induced with alloxan dose of 125 mg/kgBW, P1, P2, and P3 were given alloxan and extracts of 75, 150, and 300 mg/kgBW respectively. Rats were treated for 38 days and then terminated and epididymis were dissected. The results of the study with One Way Anova showed that there is an of administering tamarind leaf extract on the sperm morphology of diabetic male rats (p=0.000). Post Hoc Bonferroni test showed that the 150 mg/kgBW dose did not significantly different with the normal control (p=0.420) and produced the highest percentage of normal sperm morphology.